Faktor – Faktor yang Mempengaruhi Awareness pada Produk Halal di Kota dan Kabupaten Bogor - Hardiana Widyastuti; Nisa Zahra; Fitry Primadona (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Currently, halal products are one of the factors considered in the marketing process. The purpose of this study is to analyze the factors that influence the level of consumer awareness of halal food and cosmetic products in general which are modernized by religious beliefs. The research was conducted in Bogor City and Regency. SEM-PLS analysis was used in data analysis in this study. The results of the study explain that the factors that influence public awareness of halal products are factors of halal certification, halal exposure, and religious beliefs. While the factors that have no effect are health reasons. Religious belief as a moderating variable will increase the awareness factor of exposure to halal food and health causes. Religious beliefs do not reinforce or absorb the belief factors that influence people's awareness of halal food. keyword: halal, halal awareness, religious belief, halal food, halal cosmetics.